Human Umbilical Cord Mesenchymal Stem Cell Derived Exosomes Delivered Using Silk Fibroin and Sericin Composite Hydrogel Promote Wound Healing - Han, Chaoshan; Liu, Feng; Zhang, Yu; Chen, Wenjie; Luo, Wei; Ding, Fengzhi; Lu, Lin; Wu, Chengjie; Li, Yangxin (Frontiers in Cardiovascular Medicine, 2021)
Abstract Recent studies have shown that the hydrogels formed by composite biomaterials are better choice than hydrogels formed by single biomaterial for tissue repair. We explored the feasibility of the composite hydrogel formed by silk fibroin (SF) and silk sericin (SS) in tissue repair for the excellent mechanical properties of SF, and cell adhesion and biocompatible properties of SS. In our study, the SF SS hydrogel was formed by SF and SS protein with separate extraction method (LiBr dissolution for SF and hot alkaline water dissolution for SS), while SF-SS hydrogel was formed by SF and SS protein using simultaneous extraction method (LiBr dissolution for SF and SS protein). The effects of the two composite hydrogels on the release of inflammatory cytokines from macrophages and the wound were analyzed. Moreover, two hydrogels were used to encapsulate and deliver human umbilical cord mesenchymal stem cell derived exosomes (UMSC-Exo). Both SF SS and SF-SS hydrogels promoted wound healing, angiogenesis, and reduced inflammation and TNF-α secretion by macrophages. These beneficial effects were more significant in the experimental group treated by UMSC-Exo encapsulated in SF-SS hydrogel. Our study found that SF-SS hydrogel could be used as an excellent alternative to deliver exosomes for tissue repair.